2018
DOI: 10.1111/age.12628
|View full text |Cite
|
Sign up to set email alerts
|

Solexa sequencing and custom microRNA chip reveal repertoire of microRNAs in mammary gland of bovine suffering from natural infectious mastitis

Abstract: Identification of microRNAs (miRNAs), target genes and regulatory networks associated with innate immune and inflammatory responses and tissue damage is essential to elucidate the molecular and genetic mechanisms for resistance to mastitis. In this study, a combination of Solexa sequencing and custom miRNA chip approaches was used to profile the expression of miRNAs in bovine mammary gland at the late stage of natural infection with Staphylococcus aureus, a widespread mastitis pathogen. We found 383 loci corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 51 publications
2
25
0
Order By: Relevance
“…DNA methylation has a significant effect on miRNA expression, and approximately 10% of miRNA expression is regulated by DNA methylation [30]. miRNA also plays an important regulatory role in the immune and inflammatory responses of cows with mastitis [31,32]. In the present study, we examined the differentially methylated miRNAs in healthy and E. coli-infected mastitic cows.…”
Section: Discussionmentioning
confidence: 98%
“…DNA methylation has a significant effect on miRNA expression, and approximately 10% of miRNA expression is regulated by DNA methylation [30]. miRNA also plays an important regulatory role in the immune and inflammatory responses of cows with mastitis [31,32]. In the present study, we examined the differentially methylated miRNAs in healthy and E. coli-infected mastitic cows.…”
Section: Discussionmentioning
confidence: 98%
“…A comparison of milk microRNA contents with mammary gland cell profiles by small RNA sequencing (Hou et al., ; Ju et al., ; Li et al., ; Luoreng, Wang, Mei, & Zan, ; Shen et al., ) supports the epithelial origin of these microRNAs because the most enriched microRNAs in milk are also highly enriched in mammary glands cells and are of high importance for lactation (Chen et al., ; Do et al., , ; Gu et al., ; Muroya et al., ).…”
Section: Cellular Origin Of Milk Micrornasmentioning
confidence: 98%
“…Likewise, Le et al identified 11 up-regulated and three down-regulated known miRNAs in the milk exosomes of mastitic cows compared to healthy controls (11). Ju et al also analyzed the miRNA expression profiles of healthy vs. S. aureus-infected mammary glands, and detected 277 known and 49 novel miRNAs (12). Luoreng et al sequenced the mammary gland tissues of cows infected with E. coli or S. aureus and identified 1,838 miRNAs, including 580 known and 1,258 novel miRNAs (13).…”
Section: Introductionmentioning
confidence: 99%